A Novel Method for the Detection of Chlorpyrifos by Combining Quantum Dot-labeled Molecularly Imprinted Polymer with Flow Cytometry. (13th April 2018) - Zhang, Hong; Wang, Pingmei; Zhou, Qiang; Wang, Yanhong
ABSTRACT: Uniform-sized fluorescent molecularly imprinted polymers were prepared by one-step swelling and suspension polymerization, while chlorpyrifos, methacrylic acid, ethylene glycol dimethacrylate, and oil-soluble CdSe/ZnS quantum dots were used as the carrier, template molecule, functional monomer, cross-linker, and fluorophor, respectively. The morphology, adsorption dynamics, binding ability, and selectivity of quantum dot-labeled molecularly imprinted polymers were evaluated. The dosage of quantum dots for labeling the molecularly imprinted polymers was optimized. The results showed that the optimized dose of quantum dots was 200 µL using a concentration of 8.0 µM. The microsphere size was approximately 10 µm with a honeycombed surface. The quantum dot-labeled molecularly imprinted polymers had an even brightness and a high selectivity. In the presence of different concentrations of chlorpyrifos, a decrease in the fluorescence intensity of the quantum dot-labeled molecularly imprinted polymer was clearly identified by flow cytometry. The whole detection process was accomplished within 2 h including pretreatment. This method was used for the determination of chlorpyrifos in tap water samples.